(untitled) (Economics and region, 2023)
The article examines the impact of the external environment on the management of logistics enterprises. Various environmental factors are considered, namely: economic, political, socio-cultural, unforeseen events and risks, as well as situations in the international environment. We have substantiated that the external environment is a key factor that affects the success or failure of an organization. We also provide a number of examples that demonstrate the impact of various factors on enterprises in Poltava region during the war. We have concluded that for an organization to be successful, it is necessary to pay attention to the external environment and develop strategies that take into account the possible impacts of various factors. It was emphasized that it is necessary to be able to adapt to changes that may occur in the external environment and develop strategies that provide a competitive advantage.